APLIKASI TRACKING REAL TIME ANGKUTAN KOTA MEDAN BERBASIS ANDROID - Ilka Zufria; Muhammad Dedi Irawan; Suendri Suendri; Habib Asy Muhyi (JISTech (Journal of Islamic Science and Technology), 2020)
Research on information technology, namely in terms of urban transportation in Medan. This study makes information technology in the form of an android application for customers and drivers which aims to track the location of city transportation using a driver application that is directly connected online with the customer application so that they can see the position of the driver and can also request pick-up at the bus stop. In terms of tracking using GPS (Global Positioning System) while for mapping using Google Maps Api Key. This application uses the design of several Unified Modeling Language (UML) diagrams, including use case diagrams, activity diagrams, sequence diagrams and class diagrams.